Spirituality Well-Being, Health Status, Nutritional Status and Their Relation to Illness Perception in Chronic Obstructive Pulmonary Disease - Puspasari, Scholastica Fina Aryu; Kurniastuti, Margaretha; McGenggeng, Kosen d'Aristo (Universitas Muhammadiyah Surakarta, 2025)
COPD (Chronic Obstructive Pulmonary Disease) is a lung disease characterized by persistent progressive airflow limitation. COPD is one of the respiratory disorders that are often found in developed and developing countries with increasing prevalence. The purpose of this study was to determine spirituality well-being, nutritional status, and health status and their relationship to the perception of illness. This study used a quantitative correlational research design with a cross-sectional approach. The population of this study were patients at the pulmonary polyclinic of the Respira Lung Hospital Yogyakarta who suffered from COPD, totaling 100 respondents. The data collection method was carried out by distributing the Revised Illness Perception Questionnaire IPQ-R, Spiritual Well-Being Scale (SWBS), Mini Nutritional Assessment (MNA) and COPD Assessment Test (CAT) questionnaires. The results showed that 61% of respondents were male, 78% of respondents were over 55 years old, 75% of respondents were in the high spiritual well-being category, 63% of respondents had moderate health status, 35% of respondents were malnourished and at risk of malnutrition, 85% of respondents had a moderate perception of illness. The results of the bivariate test showed that the p-value for spirituality well-being (SWB), health status, and nutritional status on the perception of illness were 0.257; 0.72 and 0.28, respectively. It can be concluded that there is no relationship between SWB, health status, and nutritional status with the perception of illness in COPD patients. Suggestions are the need for family assistance in caring for COPD patients, providing diet, and the need for peer groups among COPD patients.